Aging-Associated miR-217 Aggravates Atherosclerosis and Promotes Cardiovascular Dysfunction - de Yébenes, Virginia G; Briones, Ana M; Martos-Folgado, Inmaculada; Mur, Sonia M; Oller, Jorge; Bilal, Faiz; González-Amor, María; Méndez-Barbero, Nerea; Silla-Castro, Juan Carlos; Were, Felipe; Jiménez-Borreguero, Luis J; Sánchez-Cabo, Fátima; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2020)
microRNAs are master regulators of gene expression with essential roles in virtually all biological processes. miR-217 has been associated with aging and cellular senescence, but its role in vascular disease is not understood. Approach and Results: We have used an inducible endothelium-specific knock-in mouse model to address the role of miR-217 in vascular function and atherosclerosis. miR-217 reduced NO production and promoted endothelial dysfunction, increased blood pressure, and exacerbated atherosclerosis in proatherogenic apoE-/- mice. Moreover, increased endothelial miR-217 expression led to the development of coronary artery disease and altered left ventricular heart function, inducing diastolic and systolic dysfunction. Conversely, inhibition of endogenous vascular miR-217 in apoE-/- mice improved vascular contractility and diminished atherosclerosis. Transcriptome analysis revealed that miR-217 regulates an endothelial signaling hub and downregulates a network of eNOS (endothelial NO synthase) activators, including VEGF (vascular endothelial growth factor) and apelin receptor pathways, resulting in diminished eNOS expression. Further analysis revealed that human plasma miR-217 is a biomarker of vascular aging and cardiovascular risk.OBJECTIVEmicroRNAs are master regulators of gene expression with essential roles in virtually all biological processes. miR-217 has been associated with aging and cellular senescence, but its role in vascular disease is not understood. Approach and Results: We have used an inducible endothelium-specific knock-in mouse model to address the role of miR-217 in vascular function and atherosclerosis. miR-217 reduced NO production and promoted endothelial dysfunction, increased blood pressure, and exacerbated atherosclerosis in proatherogenic apoE-/- mice. Moreover, increased endothelial miR-217 expression led to the development of coronary artery disease and altered left ventricular heart function, inducing diastolic and systolic dysfunction. Conversely, inhibition of endogenous vascular miR-217 in apoE-/- mice improved vascular contractility and diminished atherosclerosis. Transcriptome analysis revealed that miR-217 regulates an endothelial signaling hub and downregulates a network of eNOS (endothelial NO synthase) activators, including VEGF (vascular endothelial growth factor) and apelin receptor pathways, resulting in diminished eNOS expression. Further analysis revealed that human plasma miR-217 is a biomarker of vascular aging and cardiovascular risk.Our results highlight the therapeutic potential of miR-217 inhibitors in aging-related cardiovascular disease.CONCLUSIONSOur results highlight the therapeutic potential of miR-217 inhibitors in aging-related cardiovascular disease.